Effects of globalization and the future of human resources in Arab countries (المجلة العراقية للعلوم الاقتصادية, 2018)
Although there are many aspects in the global economy that differ in economic activities, local and international, that the economy is still divided into countries of the North (developed countries) and South (developing countries), for the entry into force of the law of specialization and the international division of labor. Despite the assistance and economic developments associated with the development of infrastructure of developed economies, the development of infrastructure of developing economies are still under the influence of this law. In addition, globalization has contributed directly and indirectly in the promotion of this Act under the umbrella of the technological developments and new scientific information revolution that has emerged and communication between international economies, which limit the distance (gap) between the north and south. However, it is still a big gap between the two parties, despite the benefits achieved as a result of economic globalization and technological global economy, while the negative effects of globalization on the Arab economies, directly and / or indirectly, led to an increase of the structural imbalances of economic structure and infrastructure conditions in these economies. Thus, it can not solve these problems in the manner that facilitates these countries to reach development goals, and the elimination of the gap with developed countries. So we find that these economies despite the high rates of economic growth, but where this was not linked to the promotion of development where the building, did not fit associated with the generation of employment and investment opportunities. This was not growth enhanced "the important role of public and private sectors, as far as Maazz certain sectors, especially the oil sector, enhanced to generate economic growth. This sector is facing repeated crises in the international oil market. Which led to the creation of more crises, but the problems remain unresolved. especially high rates of unemployment in size "and the percentage of" especially in the Arab labor markets. Although there are some solutions in the framework of economic policies, in general, and labor policies, in particular. But these solutions are temporary, and that it is appropriate to promote the proper construction of development.